Sideritis scardica extracts inhibit aggregation and toxicity of amyloid-β in Caenorhabditis elegans used as a model for Alzheimer's disease - Heiner, Felix; Feistel, Björn; Wink, Michael (PeerJ preprints, 2017)
Background. Beyond its traditional uses in the Balkan area, Sideritis scardica (known as Greek mountain tea, Lamiaceae) is currently extensively investigated for its pharmacological activity in the central nervous system. Antidepressant, psychostimulating, cognition-enhancing and neuroprotective properties have been described. In this study, we tested hydroalcoholic extracts of S. scardica for their potential to counteract amyloid-β toxicity and aggregation, which plays a crucial role in the pathogenesis of Alzheimer's disease. Methods. For this purpose, we have chosen the nematode Caenorhabditis elegans, which is used as a model organism for neurodegenerative diseases. The concentration of different polyphenols in extracts prepared from water, 20, 40, 50, and 70 % ethanol was analysed by HPLC. Additionally, polar and unpolar fractions were prepared from the 40 % ethanolic extract and phytochemically analysed. Results. Essentially, the contents of all measured constituents increased with the lipophilicity of the extraction solvents. Treatment of transgenic C. elegans strains expressing amyloid-β with the extracts resulted in a reduced number of peptide aggregates in the head region of the worms and alleviated toxicity of amyloid-β, observable through the degree of paralysed animals. The mid-polar extracts (40 and 50 % ethanol) turned out be the most active, decreasing the plaque number by 21 % and delaying the amyloid-β-induced paralysis by up to 3.5 h. The more lipophilic extract fractions exhibited higher activity than the hydrophilic ones. Discussion. Sideritis scardica extracts demonstrated pharmacological activity against characteristics of Alzheimer's disease also in C. elegans, supporting current efforts to assess its potential for the treatment of cognitive decline. The active principle as well as the mode of action needs to be investigated in more detail.